Employer and academic staff perceptions of science and engineering graduate competencies. Issue 1 (2nd January 2020) - Khoo, E.; Zegwaard, K; Adam, A
ABSTRACT: This paper reports on the findings from a study investigating science and engineering employers and university academic teaching staff perceptions of the competencies science and engineering recent graduates require in the workplace. Data were collected through surveys and focus group interviews of science and engineering employers and academic teaching staff. Participants rated 26 graduate competencies on how important they are for graduates entering the science and engineering workplace across three aspects: important today, important in 10 years' time, and, the perceived competency performance level of recent graduates that have entered the workplace. The findings revealed that employers thought teamwork, written communication, problem solving, oral communication, and interpersonal relationships were particularly important for today while academic teaching staff, however, viewed problem solving, written communication, critical thinking, conceptual thinking, and oral communication to be important today. The findings offer insights into the extent current preparation of science and engineering students are meeting employer expectations and highlight shifts in perceived future competencies to enhance support for student learning and employability outcomes. Implications are offered for strengthening curriculum, pedagogy and assessment approaches for workplace preparation. Finally, we discuss the limitations of the present study and how future research might resolve those limitations.